2016
DOI: 10.5350/dajpn2016290206
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between empathic responding and its clinical characteristics in patients with major depressive disorder

Abstract: Relationship between empathic responding and its clinical characteristics in patients with major depressive disorder Objective: To our knowledge, there is no study specifically examining the relation between empathic responding and clinical features in patients with major depressive disorder (MDD). Our aim was to examine cognitive and affective empathic responding in patients with MDD and to explore the possible relations between clinical features and empathy. Method:The sociodemographic and clinical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Related, insufficient sleep impairs mood. Furthermore, impaired positive mood can influence helping, in part by lowering empathic sensitivity to the needs or distress of others [71], also seen in states of clinical depression [72][73][74]. Though the reductions in helping behavior observed in Studies 1 and 2 remained significant when accounting for corresponding changes in positive and negative mood, affective changes linked to insufficient sleep may nevertheless play a moderating or mediating role in the broader deficits reported in varied prosocial behaviors linked to a lack of sleep, beyond the abatement of helping.…”
Section: Discussionmentioning
confidence: 99%
“…Related, insufficient sleep impairs mood. Furthermore, impaired positive mood can influence helping, in part by lowering empathic sensitivity to the needs or distress of others [71], also seen in states of clinical depression [72][73][74]. Though the reductions in helping behavior observed in Studies 1 and 2 remained significant when accounting for corresponding changes in positive and negative mood, affective changes linked to insufficient sleep may nevertheless play a moderating or mediating role in the broader deficits reported in varied prosocial behaviors linked to a lack of sleep, beyond the abatement of helping.…”
Section: Discussionmentioning
confidence: 99%
“…According to the emotion-specificity hypothesis, psychomotor agitation or retardation is associated with deficits in emotion recognition ( 66 ), which may be due to the low ability of empathic concern ( 67 ). Meanwhile, the impairment in empathic concern reflecting negative ruminations could make people more likely to have thoughts of death ( 68 ). As the pandemic has brought an increase in suicides and a decrease in empathy ( 69 ), strategies to show more empathic concern for others might reduce depression, particularly suicidal thoughts , during the continuity of the pandemic ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Leahy stated that rumination was associated with less comprehensibility, more guilt, less control, more demand for rationality, and less consensus with others [17]. A study conducted by Ekinci et al on patients with alcohol dependence found that rumination and anxiety symptoms were associated [25].…”
Section: Emotional Schemasmentioning
confidence: 99%
“…The belief that emotions causing loss of control in a person result in more anxiety is explained by both cognitive and emotion-focused models. The belief that one has control over one's emotions is associated with less rumination and less anxiety and depression development [25]. In a study examining the role of the emotional schemas in pathological anxiety in Iranian university students, it…”
Section: Emotional Schemasmentioning
confidence: 99%